METODE TABSYIR DALAM PENDIDIKAN ISLAM DAN URGENSINYA DALAM PENDIDIKAN MODERN - Rahimi Rahimi (Jurnal Ilmiah Peuradeun, 2014)
In education, the methods are an essential and have an urgent position (important), especially to achieve the goals and learning objectives. Methods " Tabsyir " is one method that has meant an important role in motivating children to always excited to participate in various learning activities implementation. Tabsyir in modern education is known as a favor reward (the reward) a teacher or teachers use this method aims to streamline the process of teaching and learning activities. Transformation process knowledge from a teacher to students who are considered immature should be accompanied by the application of the method in terms of rewards is now known as the reward (reward). In the paper the authors attempt to explain about the method tabsyir in Islamic education regarding understanding, position, verses and hadith that describes the method and form of the function tabsyir in Islamic and modern education.